Relationship between social support and academic stress of student-athletes in physical education programmes: a cross-sectional study - Nopiyanto, Yahya Eko; Kardi, Ipa Sari (Edu Sportivo: Indonesian Journal of Physical Education, 2026)
Background: Despite extensive research on student-athletes, limited studies have examined the relationship between social support and academic stress within physical education programmes. Objectives: The purpose of this study was to analyse the relationship between social support and academic stress in student-athletes in the physical education study programme. Methods: A cross-sectional correlational design was used with 78 student-athletes. Data was collected using a 17-item Likert-scale questionnaire measuring parental, lecturer, and coach support, as well as academic stress. This instrument consists of several indicators, including parental support (4 items), lecturer support (4 items), coach support (4 items), and academic stress (5 items). The research data were analysed quantitatively. Spearman’s rank correlation was used to analyse the correlation between social support and academic stress. Results: The results of the quantitative analysis showed that student-athletes had very high social support, with a percentage of 46.15%, and moderate academic stress, with a percentage of 32.05%. Spearman’s correlation analysis revealed a significant positive association (ρ = 0.371, p = 0.001), indicating a weak-to-moderate relationship. Conclusion: It was concluded that student-athletes had very high social support and moderate academic stress, with a positive correlation between variables and no differences in terms of gender. These findings provide preliminary insights into the association between social support and academic stress among student-athletes.